SENESCENCE- AND DEATH-RELATED ALTERATION OF CHLOROPHYLLS AND CAROTENOIDS IN MARINE PHYTOPLANKTON - William Louda J.; Liu L.; Baker E.W. (My University, 2002)
This report extends previous work (. Chlorophyll degradation during senescence and death. Organic Geochemistry 29, 1233-1251.) in which we detailed type-I (alteration) and -II (destruction) degradation of chlorophyll with representative fresh water phytoplankton. The present study covers similar experiments with marine phytoplankton, namely, a cyanobacterium (''ANA'' Anacystis sp), a coccolithophore (''COC'' Coccolithophora sp.), a dinoflagellate (''GYM'' Gymnodinium sp.) and two diatoms (''CYC'' Cyclotella meneghiniana and ''THAL'' Thalassiosira sp.). Mg loss ('pheophytinization') was rapid and continuous in all species under room-oxic conditions and slow or sporadic under anoxic conditions. The proportion of dephytylated pigments (pheophorbides-a, chlorophyllides-a), relative to the phytylated forms (chlorophyll-a, pheophytins-a), increased over the first year under room-oxic conditions and in room-anoxic conditions only in ''CYC''. Pheophorbide-a was converted to pyropheophorbide-a within 15 months only in ''THAL'' and ''ANA'', and slightly in ''COC''. After 9-15 months of oxic incubation, ''COC'' was found to contain traces of purpurin-18 phytyl ester. Consideration of carotenoid pigments is also included herein. All fucoxanthin containing species, except ''THAL'', exhibited conversion of fucoxanthin to fucoxanthinol in room-oxic conditions. Diadinoxanthin was rapidly de-epoxidized to give diatoxanthin within the first 2-4 weeks. Diatoxanthin then disappeared from all species by 15 months with a concurrent increase in a pigment which we tentatively identify as a cis-zeaxanthin. Incubations of pure cultures are found to be an effective way by which to model the early type-I reactions for both chlorophylls and carotenoids. The influence of oxygen during senescence-death and the onset of early diagenesis is of paramount importance. The absence of oxygen and, by inference, aerobic microbiota, retards the breakdown of these pigments dramatically.